INVITRO CHARACTERIZATION OF LACTIC ACID BACTERIA ISOLATED FROM THE INFANT FAECES AS POTENTIAL PROBIOTIC - SANGEETA HUIDROM; MANAB DEKA (International Journal of Pharma and Bio Sciences, 2014)
A study was designed to evaluate the invitro characteristictics of lactic acid bacteria to search for the potential probiotic from the infant faecal flora. In this study lactic acid bacteria which were isolated from the infant faeces were used to assay for their probiotic properties. They were assayed for probiotic characteristics such as low pH, bile resistance, biogenic amine, antimicrobial activity and antibiotics susceptibility. Out of the fifty five isolates, the five isolates viz. SW8, E.faecium SC10, L.acidophilus SH10, L.acidophilus SN2 and Leuconostoc. paramesenteriod ST9 displayed all the desirable probiotic properties invitro regarding their resistance to grow in low pH and bile tolerance and their antibiotic activities. The five isolates which displayed all the desirable probiotic invitro properties were selected for further invivo study by using mouse as animal model.